Empirical Analysis of Firm’s Risk by their Degree of leverages: Employ at Textile Industry of Pakistan - Raheem, Zakir; Raees, Sakheela; Zakir, Anam (Advances in Social Sciences Research Journal, 2017)
This paper measures the risk of firms with respect to their degree of total leverage (DTL), degree of operating leverage (DOL) and degree of financial leverage (DFL). This paper is more concerned with the application of proposed relationship found in literature about these theories with the level of risk by taking actual data of companies. Further, prior researchers prove this theory of DTL by using some assumptions and hypothetical data but this research has analyzed actual records of Textile Firms listed at Karachi Stock Exchange to check the durability of the theory. For this, firstly DTL, DOL and DFL of selected companies have been calculated by using their true records. Then, in the following year changes had been analyzed that whether changes occurred according to the same results as predicted by DTL or not. Result suggests that there is more variation in profits (loss) than expected according to their degrees, which shows that on average firms under consideration are riskier. At the end, this study also highlighted some factors which may cause the variation more than expected and make the firms riskier.